Isotherm and Kinetic Studies of Malachite Green by NaOH-Activated Carbon Made from Apple Waste - Balasubramaniam, Narayani; Louise, Isana Supiah Yosephine (Universitas Gadjah Mada, 2025)
Using textile dyes that seem to reach new heights has caused the waste produced to skyrocket. One is malachite green, which earned its popularity due to its vibrancy. However, the impact of malachite green has proven to be an adversary to the environment, aquaculture, and health. This experiment aims to analyze the removal of malachite green through adsorption by using activated carbon made from apple waste. Some activated carbon underwent activation with NaOH 0.5 M. We sieved these activated carbons into a 100 mesh and used the batch method to test them for optimal conditions. The concentration at equilibrium was analyzed using cyclic voltammetry. The results of these experiments are modeled into isotherm and kinetics models to help describe the adsorption. SEM-EDS, FTIR, and SAA also characterized the adsorbent samples. We found the NaOH-activated carbon to be the most efficient adsorbent, with optimum conditions of 0.3 g, 20 min, and 200 ppm. The adsorption data followed the Dubinin-Radushkevich isotherm and the pseudo second-order kinetics.